Mitochondrial ROS contribute to oridonin-induced HepG2 apoptosis through PARP activation - Liu, Xiaoning (Oncol Lett, 2018)
Oridonin, the main active constituent of Rabdosia rubescens, is known to exert antitumor activity via the induction of apoptosis in numerous types of human cancer cells. However, the underlying regulatory mechanisms of mitochondrial ROS in oridonin-induced HepG2 apoptosis remain largely unknown, due to limitations of subcellular imaging resolution. Previously, it has been suggested that mitochondria serve a potential role in sensing and signaling cellular redox changes in vital biological processes such as cell death and the abiotic stress response, based on studies involving the mitochondrial-targeted redox-sensitive green fluorescent protein (GFP). To address this, a mitochondrial-targeted Grx1-roGFP2 (mtGrx1-roGFP2) biosensor was implemented to monitor real-time mitochondrial redox changes of HepG2 cells in response to either H(2)O(2)/DTT or oridonin/SS31 treatment. It was determined that oridonin caused a perturbation in mitochondrial redox status, which in turn contributed to oridonin-induced apoptosis. Furthermore, a novel mechanism underlying the regulation of mitochondrial redox changes in oridonin-induced HepG2 apoptosis, presumably dependent on PARP cleavage, was proposed. In conclusion, the present study provides evidence in support of mitochondrial redox changes as a potential mediator in the apoptotic activities of oridonin in HepG2 cells, which provides insight into the molecular mechanisms by which mitochondrial redox signaling regulates oridonin-induced apoptosis in cancer therapy, and the development of mitochondria-specific oridonin as a promising novel anticancer therapeutic strategy.